1990
DOI: 10.1093/jmedent/27.3.377
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Sporozoite Detection by Dissection and Elisa to Assess Infectivity of Afrotropical Anopheles (Diptera: Culicidae)

Abstract: Malaria infection rates determined by dissection and Plasmodium falciparum enzyme-linked immunosorbent assay (ELISA) were compared for 26,935 Anopheles gambiae Giles sensu lato and 17,739 Anopheles funestus Giles collected during 20 mo in western Kenya. ELISA infection rates were about 43% higher than dissection sporozoite rates. In dissection-negative Anopheles, circumsporozoite (CS) protein was detected by ELISA in 5.2% of 10,017 salivary gland samples and in 12.2% of 237 thorax samples. The accuracy of diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 0 publications
0
65
0
Order By: Relevance
“…However, this may not always be the case since CS proteins in the thorax may be detected even when sporozoite infections abort before reaching the salivary glands. 22 Thus ELISA-based indices could overestimate true infectivity and may also incriminate species that are, in fact, not transmitters in the field. This could well be a factor in Sri Lanka, where in a situation of unstable malaria and low transmission rates, ELISA studies have incriminated a large number of anopheline species.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may not always be the case since CS proteins in the thorax may be detected even when sporozoite infections abort before reaching the salivary glands. 22 Thus ELISA-based indices could overestimate true infectivity and may also incriminate species that are, in fact, not transmitters in the field. This could well be a factor in Sri Lanka, where in a situation of unstable malaria and low transmission rates, ELISA studies have incriminated a large number of anopheline species.…”
Section: Discussionmentioning
confidence: 99%
“…Macdonald (1952) defined sporozoite rate as the proportion of mosquitoes with sporozoites in their salivary glands. The parameter has been used as an epidemiological index to determine the infectivity of the species of Anopheles (Beier et al, 1990). Sporozoite rate can be determined by dissection and ELISA (Adungo et al, 1991;Beier et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The parameter has been used as an epidemiological index to determine the infectivity of the species of Anopheles (Beier et al, 1990). Sporozoite rate can be determined by dissection and ELISA (Adungo et al, 1991;Beier et al, 1990). Determination of sporozoite rate by dissection has been found to be more accurate and sensitive than the ELISA method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that the detection of CSP in the head/ thorax and abdomen reflected effective infections of the salivary glands by sporozoites and of the midgut by oocysts, respectively. It has been suggested that the detection of free soluble CSP or sporozoites within the hemocoel overestimates the frequency of salivary gland infection Beier et al, 1990). If this was the case here, then most insects in which CSP was detected in the salivary glands by ELISA would be expected to have CSP throughout the entire body.…”
Section: Resultsmentioning
confidence: 74%